2002
DOI: 10.1007/s00105-001-0303-y
|View full text |Cite
|
Sign up to set email alerts
|

Unilaterale Blepharochalasis mit läsionalen IgA-Ablagerungen

Abstract: A 36-year-old male patient presented with unilateral periocular skin atrophy. The blepharochalasis developed without any obvious inflammation of the eyelids over the past 10 years. Interestingly, elongated blood vessels and microaneurysmatic vessel changes were found in the tarsal conjunctiva. A punch biopsy revealed a nearly complete loss of elastic fibres in the papillary and superficial reticular dermis. The contralateral side was histopathologically normal. On immunohistology IgA-deposits could be observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A few authors have reported the possible role of immunological mechanisms. Grassegger et al 1 and Schaeppi et al 2 detected IgA deposits in the dermis, while Schaeppi et al also found IgA in the dermo‐epidermal junction. Based on earlier in vitro studies, 7–9 Grassegger et al suggested that during the oedematus episode the change of elastic fibre structure may create neo‐antigen sites in vivo , which then induce an immune response.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A few authors have reported the possible role of immunological mechanisms. Grassegger et al 1 and Schaeppi et al 2 detected IgA deposits in the dermis, while Schaeppi et al also found IgA in the dermo‐epidermal junction. Based on earlier in vitro studies, 7–9 Grassegger et al suggested that during the oedematus episode the change of elastic fibre structure may create neo‐antigen sites in vivo , which then induce an immune response.…”
Section: Discussionmentioning
confidence: 97%
“…The number of elastic fibres also decreases in the tendons of the external orbital muscles and as a result these elongate, which leads to other ophthalmological abnormalities. The pathomechanism of the condition is not precisely known, although a few authors have suggested immunological causes 1,2 . We present the case of a young woman, who was followed for 7 years.…”
Section: Introductionmentioning
confidence: 98%